Heat-seal coating composition for paper products and application of heat-seal coating composition
By using a heat seal coating composition composed of biomass materials with dendritic or network-like structures and other polymer materials, the problems of insufficient biodegradability and heat sealing performance of heat seal coating materials of paper products are solved, and the problem of insufficient biodegradability and heat sealing performance of heat sealing coating materials of paper products is achieved. Efficient and environmentally friendly coating process reduces production costs and improves the leveling and heat sealing strength of the coating.
Patent Information
- Application Number
- CN202411486473.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-07
AI Technical Summary
The heat seal coating materials of existing paper products are difficult to achieve good biodegradability, water resistance and heat sealing properties. At the same time, the production process is complex and costly, and the coating solids content is too high and the paper deformation and viscosity increase. Affects the coating quality.
A heat-sealed coating composition consisting of dendritic or network-like biomass materials, cationic biomass materials, PHA, AKD, PGA, PLA, PBAT, cellulose esters and starch, etc., is formed by ultrasonic wave or vacuum treatment. Stable coating slurry, coated on paper products surfaces to improve mechanical strength and heat sealing properties.
Achieves a green, non-toxic, biodegradable heat sealing coating with good leveling and heat sealing properties, reducing production costs, simplifying process flow, and keeping the coating smooth and flat in a wide solids range and water blocking effects.
Smart Images

Figure CN119265999A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of paper products, and in particular relates to a heat-sealing coating composition for paper products and an application thereof. Background Art
[0002] As ecological and environmental problems become increasingly serious, environmental protection has become a mainstream value. Plastic packaging is gradually restricted because of its incomplete recyclability and biodegradability, which can cause serious ecological problems. Paper products are becoming more and more important in the field of packaging. However, due to the lack of heat sealing properties of paper products themselves, heat-sealing coatings formed by materials such as polypropylene and polyethylene are usually covered on their surfaces by lamination, leaching or coating, giving paper barrier properties and heat-sealing properties, thereby replacing plastic packaging. Paper with heat-sealing coatings not only has high mechanical strength (improves tear resistance and wear resistance), but also can form a firm sealed space after heat sealing to prevent the contents of the sealed space (food, medical supplies or other products susceptible to the environment) from leaking and maintain the integrity of the packaging, and can effectively isolate the outside air and moisture, thereby extending the shelf life of the contents.
[0003] However, materials such as polypropylene and polyethylene are petroleum-based materials, which are difficult to degrade naturally. If the microplastics formed enter the human body, they are difficult to be metabolized, which can easily induce various diseases and cause great harm to human health. At present, the heat-sealable coating structure is mainly formed by replacing petroleum-based materials with degradable polymer materials. For example: Patent document CN103774490A discloses a method of applying polylactic acid particles to paper and then hot pressing film, but the barrier property of polylactic acid film is poorer than that of traditional non-degradable polypropylene, polyethylene, and polyethylene terephthalate (PET) films, and it is necessary to further improve its barrier performance. Patent document CN107687111A pre-treats PLA fibers with cationic guar gum, although it improves the strength of bamboo fiber / PLA fiber paper to a certain extent, but the paper strength is still a certain distance from the actual packaging needs. In addition, the polylactic acid used in the above method and the cost of pre-treating PLA fibers with cationic guar gum are high, and the production process is more complicated.
[0004] In order to reduce the difficulty and cost of production, the technology of coating the surface of paper has been further developed to provide additional protection for the paper through the coating, and to increase the mechanical strength, heat sealing, water resistance, oil resistance and antibacterial properties of the paper. However, the existing coating composition for providing the coating is easy to cause paper deformation when the coating amount is large, and the viscosity of the coating is increased when the solid content is high (> 20%), which makes the leveling property worse, and it is easy to cause the coating to have coating lines and pinholes and other undesirable results; and when the coating amount is low, it is difficult to achieve the purpose of improving the performance of paper products. Summary of the invention
[0005] In order to improve the deficiencies of the prior art, the present invention aims to provide a heat-seal coating composition for paper products, which is green, non-toxic, biodegradable, water-resistant and has good heat-seal performance. This purpose is achieved by a heat-seal coating composition for paper products, the coating composition comprising:
[0006] Component A: one or both of a biomass material having a dendritic or network structure or a cationized biomass material having a dendritic or network structure;
[0007] Component B is one, two or more selected from PHA (polyhydroxyalkanoate), AKD (alkyl ketene dimer), PGA (polyglycolide), PLA (polylactide), PBAT (copolymer of butylene adipate and butylene terephthalate), cellulose ester and cellulose ether, for example, a combination of PHA and AKD;
[0008] Component C is one, two or more selected from the group consisting of thermoplastic cellulose derivatives, starchy substances, rosin, cardanol-based epoxy resins, epoxy soybean oil, epoxy castor oil, tannic acid, and malic acid.
[0009] According to a preferred embodiment of the present invention, the heat seal coating composition consists of component A, component B and component C.
[0010] According to an embodiment of the present invention, the coating composition comprises, by weight, 5 to 20 parts of component A, 25 to 50 parts of component B, and 15 to 40 parts of component C, preferably 5 to 20 parts of component A, 25 to 50 parts of component B, and 15 to 40 parts of component C, wherein component B and component C are emulsions.
[0011] As an example, the component A is a biomass having a dendritic or network structure.
[0012] As another example, the component A is a cationized biomass material having a dendritic or network structure.
[0013] As another example, the component A consists of a biomass material having a dendritic or network structure and a cationized biomass material having a dendritic or network structure.
[0014] According to an embodiment of the present invention, the component A is a mixture of 5 to 15 parts of biomass having a dendritic or network structure and 5 to 15 parts of cationized biomass materials having a dendritic or network structure, preferably, the component A is a mixture of 10 to 15 parts of biomass having a dendritic or network structure and 8 to 15 parts of cationized biomass materials having a dendritic or network structure.
[0015] According to an embodiment of the present invention, the thermoplastic cellulose derivatives include but are not limited to cellulose ethers, such as methyl cellulose, carboxymethyl cellulose, and cellulose esters, such as cellulose acetate and cellulose acetate butyrate.
[0016] According to an embodiment of the present invention, the starch material includes, but is not limited to, one, two or more of cassava starch, potato starch, corn starch, lotus root starch, oxidized starch, oil-proof starch, and the like.
[0017] According to an embodiment of the present invention, the component B includes 20 to 50 parts by mass of 35% PHA emulsion, 2 to 15 parts by mass of 10% AKD emulsion, 5 to 30 parts by mass of 20% PLA emulsion, 10 to 30 parts by mass of 25% PGA emulsion, 5 to 25 parts by mass of 35% PBAT emulsion, 3 to 15 parts by mass of 30% cellulose ester emulsion or cellulose ether emulsion, one or more of the emulsifier of the emulsion is Tween 80 or Span 80, the amount of the emulsifier is 3%-5% of the mass of the dispersion medium, and the dispersant is water.
[0018] According to an embodiment of the present invention, the component C includes 20 to 40 parts by mass of a 2% thermoplastic cellulose emulsion (ethyl cellulose, cellulose acetate, carboxymethyl cellulose, etc.), 2 to 10 parts by mass of a 5% thermoplastic starch emulsion, 2 to 15 parts by mass of a 25% rosin emulsion, 15 to 35 parts of epoxidized vegetable oil (epoxidized soybean oil or epoxidized castor oil), 5 to 15 parts of a polyacid (malic acid or tannic acid) or a combination of at least two or more of thermoplastic cellulose and thermoplastic starch or epoxidized vegetable oil and polyacid, the emulsifier of the emulsion in the component C is Tween 80 or Span 80, the amount of the emulsifier is 3%-5% of the mass of the dispersion medium, and the dispersant of the emulsion is water.
[0019] According to an embodiment of the present invention, the coating composition further comprises auxiliary materials, preferably 3 to 15 parts of auxiliary materials, more preferably 5 to 10 parts of auxiliary materials, in parts by mass.
[0020] According to an embodiment of the present invention, the auxiliary material is selected from one, two or more of montmorillonite, bentonite, polyaluminium chloride, polyethyleneimine, alum, soy protein isolate, defoamer and bactericide.
[0021] The present invention also provides a method for preparing a coating composition slurry, comprising the following steps:
[0022] The coating composition as described above is mixed with a solvent, and then treated under ultrasonic or vacuum conditions for 0.5 to 2 hours to obtain a coating composition slurry.
[0023] According to an embodiment of the present invention, the solvent is deionized water.
[0024] According to an embodiment of the present invention, the mixing temperature is 30-50°C.
[0025] According to an embodiment of the present invention, the mixing is performed under stirring conditions.
[0026] According to an embodiment of the present invention, the stirring rate is 800-3000 rpm, and the stirring time is 30-120 min, for example, stirring at a speed of 1000 rpm for 30 min.
[0027] According to an embodiment of the present invention, the preparation method comprises the following steps:
[0028] 1) Component A, component B, component C, auxiliary materials and water are mixed, and high-speed dispersed at a temperature of 30 to 50° C. and a rotation speed of 800 to 3000 rpm for 30 to 120 minutes to obtain a mixture;
[0029] 2) Treating the mixture under ultrasonic or vacuum conditions for 0.5 to 2 hours to obtain a coating mixture slurry.
[0030] According to an embodiment of the present invention, the solid content of the coating mixture slurry is 10-80%, preferably the solid content of the coating mixture slurry is 20-75%, and the viscosity of the coating mixture slurry when the solid content is 30%, 50%, 70% and 80% is 22s, 33s, 42s and 51s respectively, and the viscosity is measured by Tu-4 viscometer.
[0031] The present invention also provides application of the coating composition as a heat-sealing coating for paper products.
[0032] According to an embodiment of the present invention, the paper product includes base paper and paper-plastic finished products.
[0033] According to an embodiment of the present invention, the finished paper product is, for example, a paper cup or a packaging bag.
[0034] The present invention also provides a method for applying the heat-sealing coating composition on the surface of a paper product, comprising the following steps:
[0035] The heat-seal coating composition slurry is coated on at least one surface of a paper product material that can form a substrate to form a heat-seal coating.
[0036] According to an embodiment of the present invention, the coating is selected from conventional coating means in the art, such as machine coating or spray coating.
[0037] According to an embodiment of the present invention, after the water-based coating is applied to the surface of the material capable of forming the substrate, a drying step is further included, wherein the drying includes at least one of baking or hot pressing.
[0038] According to an embodiment of the present invention, the machine coating comprises the following steps: placing a paper product material forming a substrate on a coating machine, selecting a wire rod of 20 μm to 80 μm, a coating speed of 5 to 20 mm / min, a coating temperature of 30 to 50°C, and coating a coating mixture slurry with a solid content of 30 to 75% on the surface of the paper product material, and drying it naturally for 20 to 40 minutes or drying it in a forced air drying oven for 10 to 20 minutes after coating.
[0039] According to an embodiment of the present invention, the spraying comprises the following steps: adding a composition with a solid content of 15 to 45% to a spray gun, spraying it evenly 2 to 3 times with a spray gun, a spraying pressure of 0.25 to 0.65 MPa, and drying it naturally for 15 to 35 minutes or drying it in a forced air drying oven for 8 to 20 minutes after spraying.
[0040] The present invention also provides a paper product with a heat-seal coating, which comprises a substrate and a heat-seal coating located on at least one surface of the substrate.
[0041] According to an embodiment of the present invention, the pulp product is a paper product, such as a paper cup.
[0042] Beneficial Effects
[0043] 1) The coating composition of the present invention has good uniformity when coated on the surface of paper products because the dendritic or network structure of component A can provide suspension and stability for the composition, and thus will not cause deformation of the paper products; when the solid content of the coating composition is 10-80%, it not only has good leveling properties, but also can give the paper products heat-sealing properties. Compared with the prior art in which the viscosity of the coating increases when the solid content is high (>20%), the leveling property deteriorates, and the coating is prone to coating lines and pinholes, etc., the present invention still has good leveling properties when the solid content reaches more than 30%, and the obtained coating is smooth and flat without defects such as coating lines and pinholes.
[0044] 2) The coating composition of the present invention, due to the strong hydrophobicity and film-forming property of component B, can make the surface after coating have good water blocking effect, and the coating surface can show lotus leaf effect, Cobb 1800 The minimum can reach 10g / m 2 .
[0045] 3) The coating composition of the present invention can improve the heat-sealing function of the coating due to the good thermoplasticity of component C, and has a certain plasticizing effect. When the substrate has a heat-sealing coating, component C in the coating can melt under a certain temperature and pressure, and enter the micropores on the surface of the substrate without the heat-sealing coating in a viscous flow state, and form "wedge-shaped adhesion" after cooling and solidification; when there are two or more heat-sealing coatings in the substrate, component C between the coatings in contact with each other can melt and fuse under a certain temperature and pressure, and solidify after cooling to achieve "intermolecular adhesion".
[0046] 4) The paper products prepared by coating with the coating composition of the present invention can achieve good heat sealing properties at a heat sealing temperature of 145°C to 260°C and a heat sealing pressure of 0.2Mpa to 0.6Mpa, and the heat sealing strength can reach 12 to 18N / 15mm.
[0047] 5) The coating composition of the present invention has a simple preparation process and is easy to industrialize. The target mixture can be obtained by physical blending, which has low production cost, energy saving and environmental protection. Its good water barrier and heat sealing properties have broad application prospects in the field of paper products. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is an electron microscope image of the biomass material with a dendritic or network structure used in Example 1;
[0049] Figure 2 for Figure 1 A magnified image of
[0050] Figure 3 This is an electron microscope image of the cationic biomass material with a dendritic or network structure used in Example 2;
[0051] Figure 4 for Figure 3 A magnified image of
[0052] Figure 5 This is a diagram showing the difference in water barrier properties of the paper-based material before and after being coated with the coating composition slurry in Example 4;
[0053] Figure 6 This is a diagram showing the heat sealing effect of the paper-based material before and after being coated with the coating composition slurry in Example 4. DETAILED DESCRIPTION
[0054] [Structure of biomass materials with dendritic or network structures]
[0055] The biomass material with a dendritic or network structure includes a micron-scale structure and a nanometer-scale structure distributed on the micron-scale structure.
[0056] According to an embodiment of the present invention, the biomass material with a dendritic or network structure is a regenerated natural polymer (for example, type II cellulose, or a mixture of type II cellulose and type I cellulose), and the regenerated natural polymer includes a micron-scale structure and a nanoscale structure distributed on the micron-scale structure.
[0057] According to an embodiment of the present invention, the size of the micron-scale structure (i.e., the volume average size) is 50μm to 500μm, preferably the size of the micron-scale structure is 50μm to 300μm, and further preferably, the size of the micron-scale structure is 100μm to 200μm, for example, any value among 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, or any point value among the intermediate values formed by any two point values.
[0058] According to an embodiment of the present invention, the length of the nanoscale structure is 50nm to 800nm, preferably the length of the nanoscale structure is 100nm to 500nm, and further preferably, the length of the nanoscale structure is 200nm to 400nm, for example, any value among 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm or any point value in the middle value formed by any two point values.
[0059] According to an embodiment of the present invention, the aspect ratio of the nanoscale structure is 1:1 to 1:150, preferably the aspect ratio of the nanoscale structure is 1:1 to 1:100, more preferably the aspect ratio of the nanoscale structure is 1:10 to 1:100, for example 1:50.
[0060] According to an embodiment of the present invention, the micron-scale structure includes at least one of a micron sheet, a micron fiber, and a micron multi-level structure.
[0061] According to an embodiment of the present invention, the micron-scale structure is in a fiber or film shape, which can also be called fiberization.
[0062] According to an embodiment of the present invention, the nanoscale structures are distributed on the surface and / or edge of the microscale structure. Specifically, the nanoscale structures are densely distributed on the surface and / or edge of the microscale structure.
[0063] According to an embodiment of the present invention, the nano-scale structure is distributed on the micro-scale structure to form a flocculent shape as a whole.
[0064] According to an embodiment of the present invention, the nano-scale structure is distributed on the micro-scale structure to form an overall structure similar to a porous sponge.
[0065] According to an embodiment of the present invention, the nano-scale structure and the micro-scale structure together form a feather-like structure.
[0066] According to an embodiment of the present invention, the nanoscale structure is in the shape of villi, tentacles, whiskers or other irregular structures.
[0067] According to an embodiment of the present invention, the biomass material is in a fibrous, flaky, feathery, branchy, flocculent or porous sponge-like structure.
[0068] [Preparation of biomass materials with dendritic or network structures]
[0069] The preparation method is selected from method 1 or method 2, wherein the method 1 comprises the following steps:
[0070] dissolving the biomass in a solvent to form a biomass solution;
[0071] The biomass solution and the coagulation bath are added to a crushing device, and the two are mechanically crushed while being mixed to prepare the bio-based material; or after the mechanical crushing, the biomass material with a dendritic or network structure is prepared by filtering and washing;
[0072] The second method comprises the following steps: pouring the biomass solution into a coagulation bath to form a biomass gel; and subjecting the biomass gel to micro-nano treatment through mechanical crushing to obtain the biomass material with a dendritic or network structure.
[0073] According to an embodiment of the present invention, the reagent used in the washing step in method one and method two is selected from at least one of water, alcohol, alcohol-water mixture, HCl aqueous solution, NaOH aqueous solution, and inorganic salt aqueous solution, preferably water and / or alcohol, such as water.
[0074] According to an embodiment of the present invention, the biomass is derived from one, two or more of the following substances: cellulose or its derivatives (such as ethyl cellulose, carboxymethyl cellulose, cellulose acetate), starch or its derivatives (such as oxidized starch, modified oil-proof starch), chitosan or its derivatives (such as carboxymethyl chitosan, chitin), and alginate.
[0075] According to an embodiment of the present invention, the biomass is selected from at least one of lignin, glucan, hemicellulose, straw, plant stems and leaves, reeds, bagasse, Chinese medicine residues, tea residues, corn cobs, fruit shells, vines, branches and the like.
[0076] For example, the biomass is selected from at least one of microcrystalline cellulose, bacterial cellulose, lignin, cotton pulp, wood pulp, bamboo pulp, straw pulp, refined cotton, absorbent cotton, cotton linter, bagasse, wood and straw, etc.; preferably one or more of microcrystalline cellulose, refined cotton, absorbent cotton and wood pulp.
[0077] According to an embodiment of the present invention, the solvent for dissolving the biomass can be selected from any good solvent known in the art that can completely dissolve the biomass. Preferably, according to the different types of cellulose or cellulose-containing raw materials, the selected solvent can be selected from one or more of the following systems: organic solvents, ionic liquids, mixed solvents of ionic liquids and organic solvents, choline-type ionic liquid low eutectic solvent systems, organic solvent / salt systems, amine oxide systems (NMMO), carbamate systems, alkali / water systems, alkali / urea systems, alkali / thiourea systems, liquid ammonia / NH4SCN, organic acids, aqueous solutions of metal salts, alcohol solutions of metal salt hydrates, water-alcohol mixed solutions of metal salt hydrates, and other solvent systems.
[0078] According to an embodiment of the present invention, the coagulation bath is selected from at least one of water, alcohol, alcohol-water mixture, HCl aqueous solution, NaOH aqueous solution, and inorganic salt aqueous solution, preferably water and / or alcohol, such as water.
[0079] For example, the biomass material can be obtained by the preparation method described in the patent document application with application number 202310481795.1.
[0080] [Cationized biomass materials with dendritic or network structures]
[0081] According to an embodiment of the present invention, the cationized biomass material structure having a dendritic or network structure modified by an organic ammonium substance containing a halogenated hydrocarbon group or an epoxy group has a rich micro-nano multi-level structure, can be grafted to form a dense network at a certain temperature and time, and a large number of hydroxyl groups are distributed on the micro-nano structure to form a larger network structure.
[0082] [Preparation of cationized biomass materials with dendritic or network structures]
[0083] A biomass material solution with a dendritic or network structure is added to an alkaline aqueous solution, stirred and dissolved to obtain a biomass alkaline solution, an alcohol organic solvent is added to the biomass alkaline solution to dissolve, a cationic etherifying agent is added to carry out a grafting reaction, and washed to obtain a cationic biomass material with a dendritic or network structure.
[0084] According to an embodiment of the present invention, the alkaline aqueous solution is selected from a NaOH aqueous solution and / or a KOH aqueous solution, and the concentration of the alkaline aqueous solution is 0.1% to 3%.
[0085] According to an embodiment of the present invention, the mass concentration of the biomass having a dendritic or network structure in the alkaline solution is 2% to 10%.
[0086] According to an embodiment of the present invention, the biomass having a dendritic or network structure is reacted in an alkaline solution at a temperature of 30 to 60° C. and a reaction time of 1 to 5 hours.
[0087] According to an embodiment of the present invention, the mass ratio of the biomass alkali solution to the etherifying agent alcohol solution is 1:0.5 to 1:3.
[0088] According to an embodiment of the present invention, the cationic etherifying agent is selected from organic ammonium salts containing halogenated hydrocarbon groups or epoxy groups, such as one or more of 3-chloro-2-hydroxypropyl-trimethylammonium chloride and epoxypropyltrimethylammonium chloride.
[0089] According to an embodiment of the present invention, the alcohol organic solvent is a composite solvent of one or more of methanol, ethanol and isopropanol.
[0090] According to an embodiment of the present invention, the temperature of the grafting reaction is 25 to 75° C., and the reaction time is 6 to 48 hours.
[0091] According to an embodiment of the present invention, the grafting reaction is carried out under stirring conditions.
[0092] The following will be further described in detail with reference to specific examples of the general formula compound of the present invention and its preparation method and application. It should be understood that the following examples are only for exemplary description and explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0093] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0094] Example 1
[0095] A heat seal coating composition comprising:
[0096] Component A 15 parts: Figure 1 and Figure 2 The biomass material having a dendritic or network structure is shown;
[0097] Preparation of biomass material with dendritic or network structure: 5 parts of cotton pulp are dissolved in 95 parts of 1-allyl-3-methylimidazolium chloride, and stirred and dissolved at 70°C for 6 hours to form a biomass solution. The biomass solution and 50 parts of water are added to a crushing device, and the two are mechanically crushed while mixing, and the ionic liquid is filtered and washed to prepare a biomass material with a solid content of 2.5% and a size of 20μm to 50μm with a dendritic or network structure.
[0098] Component B 45 parts: 10 parts of AKD emulsion with a mass fraction of 10%, 5 parts of PLA emulsion with a mass fraction of 20%, and 30 parts of PHA emulsion with a mass fraction of 35%;
[0099] The emulsifier of AKD emulsion, PLA emulsion and PHA emulsion in component B is Tween 80, and the amount of the emulsifier is 5% of the mass of the dispersion medium; the dispersant of AKD emulsion, PLA emulsion and PHA emulsion is water.
[0100] Component C 35 parts: 20 parts of epoxy castor oil, 10 parts of tannic acid, and 5 parts of 30% by mass rosin emulsion.
[0101] In component C, the dispersant of the rosin emulsion is water, the emulsifier is Tween 60, and the amount of the emulsifier is 4% of the mass of the rosin.
[0102] 5 parts of auxiliary materials: 2 parts of montmorillonite, 3 parts of defoamer. The defoamer is a polyether defoamer, product number P-230, provided by Meiyu Chemical.
[0103] Preparation method of heat seal coating composition slurry:
[0104] 1) Mix the above component A, component B, component C, auxiliary materials and 60 parts of water, and disperse at high speed at 35° C. for 40 minutes at a rotation speed of 1500 rpm to obtain a mixture;
[0105] 2) The mixture was treated under ultrasonic conditions for 1 hour to obtain a uniform coating mixture slurry, wherein the solid content of the coating mixture slurry was 40%.
[0106] Taking the heat sealing of paper cups as an example, this embodiment provides a specific method of use and actual effects.
[0107] Usage: Place and fix the paper cup base paper on the coating machine, and use the heat seal coating composition slurry prepared in this example to coat it. Use a 50μm wire rod, a coating speed of 10mm / min, a coating temperature of 30°C, and dry it in a blast drying oven for 20 minutes after coating. The coating amount is 15g / m 2 , and obtain the finished paper cup.
[0108] Water barrier and heat seal test:
[0109] 1) Water barrier test
[0110] Use a paper absorbency tester to test the water absorption of finished paper cups and paper cup base paper within 30 minutes according to GBT1540-2002. (The water absorption value of paper cup base paper within 30 minutes is Cobb 1800 270g / m 2 )
[0111] 2) Heat seal test
[0112] The XLW(PC) intelligent electric tensile testing machine from Labthink was used to test the heat sealing strength of paper cup products and paper cup base paper according to QB / T 2358.
[0113] The test results are shown in Table 1:
[0114] Table 1 Kebo value and heat seal strength of the finished paper cup prepared in Example 1
[0115] serial number Test items unit Test value 1 <![CDATA[Cobb value 1800 > <![CDATA[g / m 2 ]]> 11.5 2 Heat seal strength N / 15mm 14
[0116] The heat sealing strength of the finished paper cup in this embodiment is greater than 10N / 15mm, Cobb 1800 Value is 10g / m 2 It has good water barrier and heat sealing properties.
[0117] Example 2
[0118] A heat seal coating composition comprising:
[0119] Component A: 15 parts: cationic biomass material with a dendritic or network structure;
[0120] Preparation of cationic biomass material with dendritic or network structure: 2.5 parts of the biomass material with dendritic or network structure in Example 1 are added to 195 parts of 0.12% NaOH aqueous solution, stirred at room temperature for 1 hour to obtain an alkaline dispersion of biomass, 15 parts of anhydrous ethanol are added to the alkaline dispersion of biomass, and then 2.5 parts of 2,3-epoxypropyltrimethylammonium chloride are added, and the reaction is stirred at 50°C for 10 hours. After the reaction is completed, the biomass material with a dendritic or network structure is washed with water to neutrality to obtain a cationic biomass material with a solid content of 1.2% and a size of 20μm to 50μm.
[0121] like Figure 3 and Figure 4As shown, this embodiment uses the biomass material with a dendritic or network structure in Example 1 as a raw material to prepare a cationized biomass material with a dendritic or network structure. It can be seen from the figure that before the introduction of cationic groups, the surface of the biomass material with a dendritic or network structure is a dense structure, while the surface of the cationized biomass material with a dendritic or network structure is relatively loose and has holes, and the density is reduced.
[0122] The cationic dendritic or network-structured biomass material used in this embodiment has a relatively loose surface structure and a porous structure due to the electrostatic repulsion between cationic groups. At the same time, the electrostatic effect can strengthen the binding force with paper products.
[0123] Component B 35 parts: 15 parts of 15% PGA emulsion by mass, 20 parts of 40% PHA emulsion by mass;
[0124] The emulsifier of the PGA emulsion and the PHA emulsion of component B is Tween 80, and the amount of the emulsifier is 5% of the dispersion medium; the dispersant of the PGA emulsion and the PHA emulsion is water.
[0125] Component C 40 parts: 15 parts of epoxidized soybean oil, 10 parts of malic acid, and 15 parts of 5% by mass thermoplastic starch.
[0126] 10 parts of auxiliary materials: 5 parts of polyaluminium chloride, 5 parts of bentonite.
[0127] Preparation method:
[0128] 1) Mix the above component A, component B, component C, auxiliary materials and 65 parts of water, and disperse at high speed at 40° C. for 30 min at a rotation speed of 1000 rpm to obtain a mixture;
[0129] 2) The mixture was treated under ultrasonic conditions for 0.5 h to obtain a uniform coating mixture slurry with a solid content of 35%.
[0130] Specific applications:
[0131] Taking the heat sealing of paper cups as an example, this embodiment will provide a specific method of use and actual effects.
[0132] Usage method: Place and fix the paper cup base paper on the coating machine, and use the heat-sealing coating composition slurry prepared in this example for coating. Use a 50 μm wire rod, a coating speed of 10 mm / min, and a coating amount of 15 g / m 2 The coating temperature is 30°C, and after coating, it is dried in a blast drying oven for 30 minutes to obtain a finished paper cup.
[0133] Water barrier and heat seal test:
[0134] 1) Water barrier test:
[0135] A paper absorbency tester was used to test the water absorbency of the finished paper cup within 30 minutes after coating the heat seal coating composition slurry according to GBT1540-2002.
[0136] 2) Heat seal test:
[0137] The heat seal strength of the finished paper cup coated with the heat seal coating composition slurry was tested by Labthink's XLW (PC) intelligent electric tensile testing machine according to QB / T 2358.
[0138] The test results are shown in Table 2:
[0139] Table 2 Kebo value and heat seal strength of the finished paper cups prepared in Example 2
[0140] serial number Test items unit Test value 1 <![CDATA[Cobb value 1800 > <![CDATA[g / m 2 ]]> 10.3 2 Heat seal strength N / 15mm 12.5
[0141] In this embodiment, the heat sealing strength of the finished paper cup is greater than 10N / 15mm, Cobb 1800 Value is 10g / m 2 It has good water barrier and heat sealing properties.
[0142] Example 3
[0143] Component A 20 parts: 10 parts of biomass material with a dendritic or network structure and 10 parts of cationized biomass material with a dendritic or network structure;
[0144] 10 parts of the biomass material with a dendritic or network structure prepared in Example 1 and 10 parts of the cationic biomass material with a dendritic or network structure prepared in Example 2 were mixed and dispersed at a high speed of 1000 rpm for 10 minutes to obtain a uniformly mixed biomass material.
[0145] Component B 45 parts: 5 parts of 5% by mass PLA emulsion, 5 parts of 25% by mass PGA emulsion, 25 parts of 35% by mass PBAT emulsion, and 10 parts of 35% by mass PHA emulsion;
[0146] The emulsifier in the PLA emulsion, PGA emulsion, PBAT emulsion and PHA emulsion described in component B is Span 80, and the amount of the emulsifier is 3% of the corresponding dispersion medium; the dispersant of the PLA emulsion, PGA emulsion, PBAT emulsion and PHA emulsion is water.
[0147] Component C 30 parts: 10 parts by mass of 2% ethyl cellulose emulsion, 10 parts by mass of 10% thermoplastic starch, 2 parts by mass of tannic acid, and 8 parts by mass of 25% rosin emulsion.
[0148] In the rosin emulsion of component C, the dispersant is water, the emulsifier is Span 80, and the amount of the emulsifier is 5% of the dispersion medium.
[0149] 5 parts of auxiliary materials: 3 parts of soy protein isolate, 2 parts of defoaming agent.
[0150] Preparation method:
[0151] 1) Mix the above-mentioned component A, component B, component C, auxiliary materials and 10 parts of water, and disperse at high speed at 40° C. for 50 min at a speed of 2000 rpm to obtain a mixture;
[0152] 2) The mixture was treated under ultrasonic conditions for 1.5 h to obtain a uniform coating mixture slurry.
[0153] Taking the heat sealing of paper cups as an example, this embodiment will provide a specific method of use and actual effects.
[0154] Usage: Place and fix the paper cup base paper on the coating machine, and use the above heat seal coating composition slurry for coating. Use a 50μm wire rod, a coating speed of 10mm / min, and a coating amount of 18g / m 2 The coating temperature is 30°C, and after coating, it is dried in a blast drying oven for 30 minutes to obtain a finished paper cup.
[0155] Water barrier and heat seal test:
[0156] 1) Water barrier test
[0157] A paper absorbency tester was used to test the water absorbency of the finished paper cup within 30 minutes after coating the heat seal coating composition slurry according to GBT1540-2002.
[0158] 2) Heat seal test
[0159] The heat seal strength of the finished paper cup coated with the heat seal coating composition slurry was tested by Labthink's XLW (PC) intelligent electric tensile testing machine according to QB / T 2358.
[0160] The test results are shown in Table 3:
[0161] Table 3 Kebo value and heat seal strength of the finished paper cups prepared in Example 3
[0162] serial number Test items unit Test value 1 <![CDATA[Cobb value 1800 > <![CDATA[g / m 2 ]]> 9.2 2 Heat seal strength N / 15mm 18
[0163] The finished paper cup in this embodiment has a heat seal strength greater than 10N / 15mm, Cobb 1800 Value is 10g / m 2When the component A in the composition is composed of a biomass material having a dendritic or network structure and a cationized biomass material having a dendritic or network structure, the heat sealing strength is further enhanced.
[0164] Example 4
[0165] The results of water barrier test on the surface of the original paper base material and the original paper base material coated with the coating composition of Example 2 (the coating method is the same as Example 2). The method of water barrier test is: drop 0.15 mL of clean water on the surface of the test material.
[0166] See also Figure 5 As shown on the left, after adding water droplets to the surface of the original paper base material, the water droplets quickly penetrate the surface of the substrate; see Figure 5 As shown on the right, after the original paper-based material is coated with the coating composition in Example 2, the surface exhibits a lotus leaf effect, the contact angle between the water droplet and the substrate surface is an obtuse angle, and has a good water-blocking effect.
[0167] The original paper base material and the original paper base material coated with the coating composition of Example 2 (the coating method is the same as that of Example 2) were subjected to peeling test after heat sealing. Figure 6 As shown, the surface of the original paper-based material is obviously damaged, while the original paper-based material has good heat sealing properties after being coated with the coating composition in Example 2.
[0168] Comparative Example 1
[0169] The heat-sealing films prepared by the laminating process using the existing PE (polyethylene) and PP (polypropylene) materials were tested (the two types of laminating papers were provided by Linglan New Materials). The test results are shown in Table 4:
[0170] Table 4 The heat seal value and heat seal strength of heat seal films made of PP and PE materials under the same test conditions
[0171]
[0172] From the above, it can be seen that the heat-sealing coating composition in the present invention is completely composed of biodegradable materials, is green, environmentally friendly and non-toxic, has good leveling and coating effects within a wide solid content range (10% to 70%), and has excellent water barrier properties (low Cobb value) and high heat sealing strength (greater than 10N / 15mm).
[0173] Compared with PE (polyethylene), PP (polypropylene) and other materials in the prior art, which need to be prepared through processes such as lamination to prepare a heat-sealing layer, the heat-sealing coating composition in the present invention can be prepared into a heat-sealing layer through a simple coating operation. The preparation process of the present invention is simple and easy to industrialize. The target mixture can be obtained by physical blending. The production cost is low, energy-saving and environmentally friendly. Its good water barrier and heat sealing properties have broad application prospects in the field of paper products.
[0174] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A heat-seal coating composition for paper products, characterized in that: The coating composition comprises: Component A: one or both of a biomass material having a dendritic or network structure or a cationized biomass material having a dendritic or network structure; Component B is one, two or more selected from the group consisting of polyhydroxyalkanoates, alkyl ketene dimers, polyglycolides, polylactides, copolymers of butylene adipate and butylene terephthalate, cellulose esters and cellulose ethers; Component C is one, two or more selected from the group consisting of thermoplastic cellulose and its derivatives, thermoplastic starch, rosin, cardanol-based epoxy resin, epoxy soybean oil, epoxy castor oil, tannic acid and malic acid.
2. The heat-sealing coating composition for paper products according to claim 1, characterized in that: The heat-sealing coating composition consists of component A, component B and component C. Preferably, the coating composition is composed of 5 to 20 parts of component A, 25 to 50 parts of component B, and 15 to 40 parts of component C in parts by weight, and the components B and C are emulsions.
3. The heat-sealing coating composition for paper products according to claim 1, characterized in that: In parts by weight, the component A is a mixture of 5 to 15 parts of biomass having a dendritic or network structure and 5 to 15 parts of cationized biomass materials having a dendritic or network structure. Preferably, the component A is a mixture of 10 to 15 parts of biomass having a dendritic or network structure and 8 to 15 parts of cationized biomass materials having a dendritic or network structure. Preferably, the component B includes one or more of 20 to 50 parts by mass of a 35% PHA emulsion, 2 to 15 parts by mass of a 10% AKD emulsion, 5 to 30 parts by mass of a 20% PLA emulsion, 10 to 30 parts by mass of a 25% PGA emulsion, 5 to 25 parts by mass of a 35% PBAT emulsion, and 3 to 15 parts by mass of a 20% cellulose ester emulsion or a cellulose ether emulsion, the emulsifier of the emulsion is Tween 80 or Span 80, the amount of the emulsifier is 3%-5% of the mass of the dispersion medium, and the dispersant is water. Preferably, the component C comprises 20 to 40 parts by mass of a 2% thermoplastic cellulose emulsion (ethyl cellulose, cellulose acetate, carboxymethyl cellulose, etc.), 2 to 10 parts by mass of a 5% thermoplastic starch emulsion, 2 to 15 parts by mass of a 25% rosin emulsion, 15 to 35 parts of epoxidized vegetable oil, 5 to 15 parts of one of polyacids or a combination of at least two or more of thermoplastic cellulose and thermoplastic starch or epoxidized vegetable oil and polyacid, the emulsifier of the emulsion is Tween 80 or Span 80, the amount of the emulsifier is 3%-5% of the mass of the dispersion medium, and the dispersant of the emulsion is water.
4. The heat-sealing coating composition for paper products according to claim 1 or 2, characterized in that: The coating composition further comprises 3 to 15 parts of auxiliary materials by mass. Preferably, the auxiliary material is selected from one, two or more of montmorillonite, bentonite, polyaluminium chloride, polyethyleneimine, alum, soy protein isolate, defoamer and bactericide.
5. A method for preparing the coating composition slurry according to any one of claims 1 to 4, characterized in that: The following steps are involved: The coating composition according to any one of claims 1 to 4 is mixed with a solvent, and then treated under ultrasonic or vacuum conditions for 0.5 to 2 hours to obtain a coating composition slurry.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the coating composition to the solvent is 1:(1-3). Preferably, the solvent is deionized water. Preferably, the mixing temperature is 30-50°C.
7. The preparation method according to claim 5, characterized in that: The preparation method comprises the following steps: 1) Component A, component B, component C, auxiliary materials and water are mixed, and high-speed dispersed at a temperature of 30 to 50° C. and a rotation speed of 800 to 3000 rpm for 30 to 120 minutes to obtain a mixture; 2) Treating the mixture under ultrasonic or vacuum conditions for 0.5 to 2 hours to obtain a coating mixture slurry. Preferably, the solid content of the coating mixture slurry is 10-80%.
8. A method for applying the heat-seal coating composition according to any one of claims 1 to 4 or the heat-seal coating composition prepared by the method according to any one of claims 5 to 7 to the surface of a paper product, characterized in that: The steps include: The heat-seal coating composition slurry is coated on at least one surface of a paper product material that can form a substrate to form a heat-seal coating. Preferably, after the water-based coating is applied to the surface of the material that can form the substrate, a drying step is further included, wherein the drying includes at least one of baking or hot pressing.
9. The method for applying a heat-sealing coating composition to the surface of a paper product according to claim 8, characterized in that: The coating is selected from machine coating or spray coating; Preferably, the machine coating comprises the following steps: placing a paper product material forming a substrate on a coating machine, selecting a wire rod of 20 μm to 80 μm, a coating speed of 5 to 20 mm / min, a coating temperature of 30 to 50° C., coating a coating mixture slurry with a solid content of 30 to 75% on the surface of the paper product material, and drying it naturally for 20 to 40 minutes or drying it in a forced air drying oven for 10 to 20 minutes after coating. Preferably, the spraying comprises the following steps: adding a composition with a solid content of 15-45% to a spray gun, spraying evenly 2-3 times with the spray gun, with a spraying pressure of 0.25-0.65 MPa, and drying naturally for 15-35 minutes or drying in a forced air drying oven for 8-20 minutes after spraying.
10. A paper product with a heat-seal coating, comprising a substrate and a heat-seal coating located on at least one surface of the substrate.
Citation Information
Patent Citations
Preparation method of polylactic acid plastic-coated paper
CN103774490A
High-strength environment-friendly paper and preparation method and application thereof
CN107687111A
Biomass-based reinforcing agent for paper and application of biomass-based reinforcing agent
CN121473165A
High-barrier biodegradable material as well as preparation method and application thereof
CN114573965A
Waterproof oleophobic environment-friendly coating for paper products and preparation method of waterproof oleophobic environment-friendly coating
CN115928489A
Cited By
Bacteriostatic and antiviral bamboo pulp paper-based sanitary isolation bag as well as preparation method and application thereof
CN121496782A
Bacteriostatic and antiviral bamboo pulp paper-based hygiene isolation bag and preparation method and application thereof
CN121496782B
PHA-nano rosin synergistic high-barrier water-based coating as well as preparation and application thereof
CN121827133A
Pha-nanoscale rosin synergistic high-barrier water-based coating and preparation and application thereof
CN121827133B
PHA plant-based composite aqueous emulsion as well as preparation method and application thereof
CN122103613A